2012
DOI: 10.1074/jbc.m112.382226
|View full text |Cite
|
Sign up to set email alerts
|

trans-(−)-ε-Viniferin Increases Mitochondrial Sirtuin 3 (SIRT3), Activates AMP-activated Protein Kinase (AMPK), and Protects Cells in Models of Huntington Disease

Abstract: Background: Mitochondrial dysfunction is a key event mediating mutant Htt-induced neurotoxicity. Results: trans-(Ϫ)-⑀-Viniferin attenuates mutantHtt-induced SIRT3 depletion, activates AMPK, and preserves mitochondrial function. Conclusion: Increasing SIRT3 protects cells in HD.Significance: The result suggests a promising new target for development of HD therapeutics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
144
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 192 publications
(149 citation statements)
references
References 57 publications
5
144
0
Order By: Relevance
“…Accumulating evidence suggests Sirt3 plays a role in various neurodegenerative diseases (16,21,33,51,56), but whether and how Sirt3 mediates DAergic neuronal death in PD remains This article has been peer-reviewed and accepted for publication, but has yet to undergo copyediting and proof correction. The final published version may differ from this proof.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accumulating evidence suggests Sirt3 plays a role in various neurodegenerative diseases (16,21,33,51,56), but whether and how Sirt3 mediates DAergic neuronal death in PD remains This article has been peer-reviewed and accepted for publication, but has yet to undergo copyediting and proof correction. The final published version may differ from this proof.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies also have shown that Sirt3 can regulate mitochondrial ROS levels by deacetylating SOD2 (9,27,41). Recent evidence suggests that Sirt3 has a positive role in several neurological disorders, including Alzheimer's disease (21,56), Parkinson's disease (33), Huntington's disease (16) and Amyotrophic lateral sclerosis (51), but the detailed mechanism is still unknown. Mitochondrial protein acetylation plays a key role in mitochondrial dysfunction, which is a key feature of DAergic neuronal loss in PD.…”
Section: Energy Status Is a Known Determinant Of Neuronal Death (36)mentioning
confidence: 99%
“…Consistent with the cytoprotective effects resulting from Sirt3 over-expression in cultured cell lines, Kim et al (2011) demonstrated Sirt3 over-expression protects cultured mouse cortical neurons from NMDA-induced excitotoxicity and Song et al, 2013 reported Sirt3 over-expression protects spinal cord motor neurons from death in SOD1 G93A -induced toxicity model of an amyotrophic lateral sclerosis (ALS). More recently, the neuroprotective effects of viniferin, a resveratrol-derived compound, were linked to Sirt3 activation in striatal cells from a Huntington disease model (Fu et al, 2012), and Weir et al (2013) reported that Sirt3 over-expression increased the life span of primary hippocampal neurons following treatment with antimycin A. However, decreased viability has also been observed in neurons over-expressing Sirt3, as Pfister et al (2008) reported Sirt3 overexpression increased the sensitivity of cultured cerebellar granule neurons to degeneration induced by low-potassium culture conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Others reported that SIRT3 protection is mediated through its interaction with forkhead box O3 (FOXO3) transcription factors activating detoxifying genes such as catalase and manganese superoxide dismutase (MnSOD) [218]. It was observed that SIRT3 protects against mitochondrial fragmentation and neuronal cell death occurring in cells overexpressing SOD1 G93A, a model of amyotrophic lateral sclerosis (ALS) [219] and, more recently, the use of the natural compound viniferin, was demonstrated to increase SIRT3 levels causing deacetylation of MnSOD and serine/threonine kinase 11 (LKB) [220], which induced the activation of AMP-activated protein kinase increasing mitochondrial biogenesis and cell survival in HD models [220]. A recent study demonstrated that the neurotrophin pituitary adenylate cyclase activating polypeptide (PACAP) and SIRT3 expression is reduced in human and mice AD brains, this reduction being inversely correlated with Ab and tau protein levels [221].…”
Section: Mitochondrial Transport Deficienciesmentioning
confidence: 98%